Value of diffusion-weighted imaging combined with conventional magnetic resonance imaging in the diagnosis of thecomas and their differential diagnosis with adult granulosa cell tumors. (November 2019) - Fang, Mengshi; Dong, Jiangning; Zhong, Qun; Fang, Xin; Chen, Yulan; Wang, Chuanbin; Yan, Hong
Abstract: Background: Magnetic resonance imaging (MRI) is a significant method of identifying ovarian tumors, when combined with certain functional imaging techniques that have been considered to be more accurate. Purpose: Our study aims to determine the value of diffusion-weighted imaging (DWI) combined with MRI in the diagnosis of thecomas and adult ovarian granulosa cell tumors (GCTs). Material and Methods: In total, this study included 10 patients with thecomas and nine with adult GCTs. We analyzed the clinical characteristics, conventional MRI, and apparent diffusion coefficient (ADC) values of two groups. The methods of statistical analysis were univariate analysis and the receiver operating characteristic curve. Results: According to T2-weighted imaging of the solid region of the mass, 80% (8/10) of thecomas showed slightly hypointense or mixed signals, but all adult GCTs showed slightly hyperintense signals. The two groups exhibited statistically significant differences ( P  < 0.05) in morphology; presence of bleeding; the longest diameter of the cystic region; the ADC value; and the enhancement degrees of the venous and delayed periods. The mean ADC value for the thecoma group (1.30 ± 0.25 × 10 −3 mm 2 /s) was greater than that for adult GCT group (0.87 ± 0.28 × 10 −3 mm 2 /s) ( P  < 0.05), and the cut-off value was 1.055 × 10 −3 mm 2 /s (AUC = 0.900, 95% CI = 0.675–0.989). Conclusion: The combination of DWI and conventional MRI is of great value in the diagnosis of thecomas and their differential diagnosis with adult GCTs.